Peran Regulasi Emosi dan Perhatian Orang Tua pada Social Problem-Solving Remaja yang Bersekolah Asrama - Arifatul Bahirah; Rin Widya Agustin; Rini Setyowati; Tukhas Shilul Imaroh (Universitas Mathla'ul Anwar Banten, 2019)
THE ROLE OF EMOTION REGULATION AND PARENTAL ATTENTION ON SOCIAL PROBLEM-SOLVING OF BOARDING SCHOOL'S ADOLESCENT. This study aimed to know the correlation of emotion regulation and parental attention to social problem solving of boarding school adolescents. The research subjects were 65 students of SMAN CMBBS who were selected by simple random sampling method. The instruments used are social problem-solving scale, emotion regulation scale, and parental attention scale. Data were analyzed by multiple regression analysis. The results showed that there was a significant correlation between emotion regulation and parental attention with social problem solving for SMAN CMBBS adolescents, with p = 0.00 (R = 0.699). Partial correlation test proves that there is a significant correlation between emotional regulation and social problem solving for SMAN CMBBS adolescents (p = 0.00; rx1y = 0.549). Partial correlation also proves that there is a significant relationship of parental attention to social problem solving for adolescent CMBBS (p = 0.032; rx2y = 0.268). This study concludes that there is a significant correlation between emotion regulation and parental attention to social problem solving of SMAN CMBBS adolescents.